Impact of dural hypoplasia in a patient with spontaneous cerebrospinal fluid leak at atlantoaxial level - Takehiro Kitagawa; Tatsuya Ohtonari; Yu Muroya; Hiroshi Miyachi; Junkoh Yamamoto (Interdisciplinary Neurosurgery, 2021)
Cerebrospinal fluid (CSF) leak from the spinal subarachnoid space causes spontaneous intracranial hypotension; however, its pathogenesis remains unclear. We report an interesting case which had incidental lacerations of arachnoid membrane with congenital-suspected huge dural defects at C1-2 level. A 41-year-old man visited our hospital with chronic orthostatic headache and neck pain, complicated with bilateral chronic subdural hematoma (CSDH). We performed the evacuation of right CSDH. Thereafter, we identified CSF leakage at C1-2 level with computed tomographic myelography. In this surgery, we observed the laceration of arachnoid membrane with huge dural defects at bilateral dorsal to lateral sides of dura matter. We controlled CSF leak completely using DuraGen® and Adherus Dural Sealant®. Considering the histological structure of arachnoid membrane, the existence of tight junctions in this layer keeps CSF into the subarachnoid space. This case strongly indicates the congenital hypoplasia of spinal dura matter as one of causes of CSF leak. Furthermore, incidental laceration of arachnoid membrane at this portion is suspected as the cause of CSF-leak onset.